In vitro antibacterial activity Of Eurycoma longifolia Jack (Tongkat Ali) root extract - Faisal, Ghasak Ghazi; Zakaria, Siti Mastura; Najmuldeen, Ghazi Faisal (2016)
Abstract: Currently, researchers are aiming to explore herbal plants to replace synthetic drugs because herbal plants contain high active compounds and fewer side effects. Our study was done to determine the antibacterial activity of Eurycoma longifolia Jack (E. longifolia) root using ethanol based extraction method. Five types of pathogenic bacterial strains were used; Gram-positive (Staphylococcus aureus and Bacillus cereus) and Gram-negative (Escherichia coli, Salmonella typhi and Pseudomonas aeruginosa). Disc diffusion assay and Minimum Inhibitory Concentration (MIC) tests were used to determine the inhibition zone and turbidity of suspension which reflects the antibacterial activity of the extract. The ethanolic extract of E. longifolia Jack root extract showed positive results against Gram-positive bacteria (S. aureus and B. cereus) and Gram-negative (S. typhi). B.cereus and S.typhi showed inhibition zone values of 11.76mm and 14.33mm at the extract concentration of 150mg/ml that were higher than the positive control values (9.00, 12.67mm) respectively. However, E. coli and P. aeruginosa did not show any inhibition by the ethanol-based extract. From the results we can conclude that E.Longifolia root extract possess antibacterial activity that can be further explored to produce new medicinal products